Development co-operation : efforts and policies of the members of the Development Assistance Committee;1986 report - Wheeler, Joseph C.; Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1986)
This book contains report of aid issues reported by the Chairman of OECD's Development Assistance Committee. It includes analysis of recent trends in national and multilateral aid policies and of specific questions such as aid for food, refugees and energy development.
Includes bibliographic references
usc 04/10/18
Loans
Keywords: Economic assistance; Technical assistance; Economic history; International cooperation; Developing countries